STUDENTS’ LEARNING APPROACH IN THE EFL ONLINE LEARNING CONTEXT - Alit Tri Santika Ningsih; Made Hery Santosa; I Putu Ngurah Wage Myartawan (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2022)
The switching between conventional learning to online learning during this pandemic quite affected the learning approach adopted by students. This study aims to determine the learning approach of the eighth-grade students at one of public schools in Bali during online learning. The mixed-method was used in this study with two instruments for data collection: the R-SPQ-2F questionnaire and semi-structured interviews. This study involved 168 eighth grade students of one public junior high school in Bali. The analysis of the mean score of R-SPQ-2F was used to evaluate the data from questionnaire, while the interactive model analysis was used to analyze the interview data. Based on the findings, the learning method of the eight-grade students in the context of online learning tends to be of deep approach. The results of the interview revealed that the student learning approach was influenced by several supporting and inhibiting factors. This shows that student learning approaches can adapt and be influenced by various factors faced by students during the learning process. These factors can come from within students and students’ learning environment. Therefore, teachers should have a better understanding of learning approaches adopted by students during online learning situations to assist students in achieving learning success.Keywords: EFL, online learning, students’ learning approach